Dominant Factor of Household Food Security During COVID-19 Pandemic in Depok City in 2020 (Analysis of Secondary Data 2020) - Intan Hidayah; Sandra Fikawati (Amerta Nutrition, 2021)
Background: Food security is a condition when everybody has adequate physical and economical access to get nutritious and safe food to lead healthy and active life. COVID-19 pandemic can cause food security disruptions. This is because several people have lost their jobs and income so that they are no longer able to meet their food needs. Objectives: This study aimed to determine the dominant factor related to food security during COVID-19 pandemic in Depok City in 2020.Methods: This quantitative research used cross-sectional study. The data used was secondary data from the research entitled Situation of Family Food Security and Coping Mechanisms in COVID-19 Pandemic Situation in Urban and Semi-Urban Areas. The total of samples for this secondary study were 259 households who had pregnant mother, breastfeeding mother, infant or toddler. Sampling process from the primary research was carried out by purposive sampling. Researchers disseminated research information through social media and posyandu cadres and then conducted screening. Respondents who met the screening requirements would be sent an electronic mail or Whatsapp containing a research questionnaire. Data was analyzed using McNemar test, chi-square test and multiple logistic regression test.Results: This study indicated that 61.8% of households in Depok City experienced food insecurity. The results of the bivariate analysis showed that household income during pandemic, husband’s and wife’s education, the number of high educated people in household significantly related to household food security during COVID-19 pandemic. The dominant factor of household food security during the COVID-19 pandemic in Depok City in 2020 was wife’s education (OR=3.978) after being controlled by the wife’s occupation during pandemic, household income during pandemic, and husband’s education.Conclusions: Households with low educated wife were at risk to be food insecure 4 times higher than households with high educated wives.